UTILIZATION OF SKIPJACK TUNA BONE WASTE INTO FISH BONE MEAL IN LAHA VILLAGE, AMBON BAY - Kaliky, Nurainy; Wally, Pramita; Nurlette, Hartono; Wasahua, Tahir (STAI Darul Qalam Tangerang, 2025)
The utilization of skipjack tuna bone waste from this community service activity aims to raise awareness of the Laha Village community in Ambon Bay about the importance of preserving the surrounding environment in order to avoid environmental pollution in the form of bad odors from fish bone waste that is simply thrown away. This fish bone waste can come from households or home industries. The method used in this community service is Observation, participation and training. This community service was attended by 41 people consisting of lecturers and the surrounding community and was carried out smoothly according to the prepared activity plan. This fish bone flour making training activity can increase the empowerment of the local community to become more independent in utilizing fish bone waste that has economic value so that it can increase family income.